Sodium alginate reinforced polyacrylamide/xanthan gum double network ionic hydrogels for stress sensing and self-powered wearable device applications - Li, Tuo; Wei, Huige; Zhang, Yingying; Wan, Tong; Cui, Dapeng; Zhao, Shixiang; Zhang, Teng; Ji, Yanxiu; Algadi, Hassan; Guo, Zhanhu; Chu, Liqiang; Cheng, Bowen (Carbohydrate polymers, 2023)
Strong and ductile sodium alginate (SA) reinforced polyacrylamide (PAM)/xanthan gum (XG) double network ionic hydrogels were constructed for stress sensing and self-powered wearable device applications. In the designed network of PXS-Mn+/LiCl (short for PAM/XG/SA-Mn+/LiCl, where Mn+ stands for Fe3+, Cu2+ or Zn2+), PAM acts as a flexible hydrophilic skeleton, and XG functions as a ductile second network. The macromolecule SA interacts with metal ion Mn+ to form a unique complex structure, significantly improving the mechanical strength of the hydrogel. The addition of inorganic salt LiCl endows the hydrogel with high electrical conductivity, and meanwhile reduces the freezing point and prevents water loss of the hydrogel. PXS-Mn+/LiCl exhibits excellent mechanical properties and ultra-high ductility (a fracture tensile strength up to 0.65 MPa and a fracture strain up to 1800%), and high stress-sensing performance (a high GF up to 4.56 and pressure sensitivity of 0.122). Moreover, a self-powered device with a dual-power-supply mode, i.e., PXS-Mn+/LiCl-based primary battery and TENG, and a capacitor as the energy storage component was constructed, which shows promising prospects for self-powered wearable electronics. [Display omitted]